The Influence of Entrepreneurship Learning on Students' Entrepreneurial Interest - Miranda Sumaila; Radia Hafid; Maya Novrita Dama; Meyko Panigoro; Ririend Koniyo (Badan Penerbit STIEPARI Press, 2025)
This study aims to discover the influence of enterpreneurship learning on students entrepreneurial interest at SMK Negeri 2 Paguyaman. This study employs a quantitative approach using an Associative study method. The data used in this study are primary data obtained through the distribution of questionnaires to all Class XI students of SMK Negeri 2 Paguyaman. The samples consist of 90 respondents. The data were analyzed using simple linear regression. The results of the data aanalysis indicate that entrepreneurship learning significantly influences students entrepreneurial interest at SMK Negeri 2 Paguyaman. The contribution of enterpreneurship learning entrepreneurial interest in 88,5% while the remaining 11,5% is influenced by other variables not exantited inthis study.